Optimal Portfolio Based Risk and Return of Corporate Sukuk in Indonesia - Wahyu Rosid; Idqan Fahmi; Rifki Ismal (Budapest International Research and Critics University, 2022)
This study aims to analyze the optimal portfolio of corporate sukuk in Indonesia using the risk return analysis approach and the CML (Capital Market Line) model in order to foster investor interest in investing in corporate sukuk instruments. This research was conducted using data throughout 2014 – 2018 and is divided into three measurement periods, namely the crisis period (2014-2016), post-crisis (2016-2018) and long-term (2014-2018), each period representing Indonesia's economic condition. and globally. The results showed that during the crisis period, sukuk with ijarah were superior both in risk and return compared to mudharabah, so that the optimal portfolio composition was to maximize the composition of ijarah. However, in the post-crisis period (improvement of economic conditions) and long-term measurements, the composition of the existing portfolio is more varied depending on the goals of each investor, either to maximize returns or to minimize risk. However, in the post-crisis period (improvement of economic conditions) and long-term measurements, the composition of the existing portfolio is more varied depending on the goals of each investor, either to maximize returns or to minimize risk. The optimal portfolio combination (referring to the benchmark rate) between sukuk mudharabah and sukuk ijarah is 0% mudharabah: 100% ijarah for the period 2014 – 2016 with a return rate of 3.9 and a risk of 0.49, 81% mudharabah : 19% ijarah for the period 2016 – 2018 with a return rate of 2.71 and a risk of 0.65, and 85% mudharabah: 15% ijarah for the period 2014 – 2018 with a return rate of 2.77 and a risk of 0.79. This combination can form an efficient frontier that provides a comparison of the same level of return and risk.